Safety and Feasibility of an Early Mobilization Protocol for Patients with Femoral Intra-Aortic Balloon Pumps as Bridge to Heart Transplant. Issue 5 (6th August 2021) - Chen, Stacey; Lester, Lynette; Piper, Greta L.; Toy, Bridget; Saputo, Mary; Chan, Wendy; Fischer, Mary G.; Gidea, Claudia; Kon, Zachary N.; Moazami, Nader; Smith, Deane E.
Abstract : Intra-aortic balloon pumps (IABPs) can be used to provide hemodynamic support in patients with end-stage heart failure as a bridge to transplantation (BTT). The IABP is commonly inserted via the common femoral artery, which can limit patients' mobility. The Ramsey protocol, developed by a critical care physical therapist, allows patients with femoral IABPs to ambulate with the assistance of a tilt table. The aim of this study was to determine the safety and feasibility of a modified Ramsey protocol for early mobilization of patients with femoral IABPs as BTT. This is a retrospective single-center review of patients with femoral IABPs as BTT using a tilt table protocol from May 2019 to May 2020. Primary outcomes were time to successful ambulation, number of successful ambulation events, and ambulation-associated adverse events, including IABP augmentation, waveform, positioning changes, and vascular complications at the insertion site. Twenty-four patients (mean age 55 ± 16 years) underwent femoral IABP insertion as BTT and were mobilized following our protocol. Nineteen patients (79.2%) successfully ambulated with a median of three sessions (interquartile range, 2–4) per patient. The median time from IABP insertion to ambulation was 3 days (interquartile range, 2–5). Twenty-one patients underwent heart transplantation, of which all 19 who ambulated were successfully bridged to transplantation. Early mobilization in select patients with femoral IABPs can be performed safely and successfully, avoiding the deleterious effects of bed rest that have been historically seen in this patient population.